Hover: Exploring cognitive maps and mid-air pointing for television control. Issue 129 (September 2019) - Popovici, Irina; Schipor, Ovidiu-Andrei; Vatavu, Radu-Daniel
Highlights: We introduce Hover, a new concept and gesture user interface for smart TVs. We evaluate user performance for recalling and pointing to loci in mid-air. We discuss Hover in terms of interaction dimensions and qualities desirable for air pointing. Abstract: We introduce "Hover, " a new concept and interface for remote TV control based on air pointing in the users' personal, peripersonal, and extrapersonal space and implemented with mid-air spatial shortcuts to viewers' preferred TV channels distributed in the room with no representation other than that created in users' own imagination. Hover exploits memory and spatial orientation skills to enable fast access to TV channels with a mere pointing of the hand in mid-air. A controlled experiment with 17 participants and 9 mid-air loci corresponding to shortcuts to television channels revealed an average user recall rate of 80% and individual rates up to 100% for mid-air loci, pointing accuracy offsets of 10 cm, and 99% recognition rate for air pointing actions. We hope that Hover will inspire researchers and practitioners of user interfaces for smart TVs to consider spatial locations and mid-air as active elements to design new interactive experiences for home entertainment environments centered on the smart TV.